PENINGKATAN KEMAMPUAN MEMBACA PEMAHAMAN MELALUIPEMBELAJARAN PROBLEM BASED LEARNINGBERBANTU MEDIA BIG BOOK DI KELAS IV SD NEGERI 5 NISAM - Quratul Aini; Syahrin, Alfi; Darwis, Muhammad (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe the improvement of reading comprehension skills among fourth-grade students at SD Negeri 5 Nisam through the implementation of the Problem Based Learning (PBL) model assisted by Big Book media. The background of this study is based on students' low reading comprehension ability, as they still had trouble analyzing, constructing information, and summarizing the content of a text, resulting in Indonesian language learning outcomes that had not yet reached the established Learning Objective Mastery Criteria (KKTP). This study employed a qualitative approach in the form of Classroom Action Research (CAR), carried out in two cycles consisting of planning, action implementation, observation, and reflection. The research subjects were 19 fourth-grade students of SD Negeri 5 Nisam. Data were collected through learning outcome tests, observation sheets of teacher and student activities, and interviews, then analyzed using descriptive quantitative and qualitative methods. The results showed that the percentage of students' learning completeness increased from 63.15% in Cycle I to 89.47% in Cycle II, thereby achieving the 80% classical completeness target. Teacher activity increased from 95% to 96%, while student activity increased from 97% to 98%, both falling into the very good category. Interview results also indicated that students gave positive responses to the use of Big Book media and the PBL model, finding the learning process more engaging, easier to understand, and enjoyable. Based on these findings, it can be concluded that the implementation of the Problem Based Learning model assisted by Big Book media is effective in improving reading comprehension skills and increasing student engagement in elementary Indonesian language learning.